PERBANDINGANHASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH (MM) DANTEAM GAMES TOURNAMENT (TGT) PADA MATA PELAJARAN KIMIA DI KELAS X IPA MAN 1 KOTA BENGKULU - Nova Syofiana; Salastri Rohiat; Hermansyah Amir (University of Bengkulu, 2018)
This study aimed to determine differences in students’learning outcomes using cooperative learning model with Make A match and Team Games Tournament on chemistry subject of X IPA in MAN 1 Kota Bengkulu.A quasi-experimental (quasi experiment) was used as research model.Population of this research was all of X IPA students which was137 students,then,there were 74 students as sample of this research taken from two classes, X IPA1 and X IPA 3.The techniques in data analysis used mean value,questionnaire analysis,normality test,homogeneity test,and t-test with significant ? = 0,05.The data collecting technique was done by usinga SPSS16 program for windows.The data on students learning outcomes were seen by differences between pre-test and post-test.Experiment 1class had 47.44 as the average of the differences and Experiment 2 class had43.79 as the average of the differences.The result showed that the students learning outcomes were influenced by learning motivation.Additionally,the data of students learning outcomes in both classes obtained from the learning motivation percentage which were 83,84% categorized as very good and 7,49% as good.From the resultof this study,it could be concluded that, generally,either the learning outcomes or students learning motivation in applying cooperative learning model,TGT type is higher than MM type.It showed that t count > t table,where 1.7515 > 1.6662 forlearning outcomes and 8.9804 > 1.6662 for students learning motivation.In the sameway,there is a significant difference between learning outcomes and students learning motivation by applying cooperative learning model in two types,namely Make A Match (MM) and Team Games Tournament (TGT).